Digitalisasi Pengelolaan Data UMKM Milkshake Pakuan Melalui Sistem Database Microsoft Access - Gefri, Roofif Ikhsanul; Fatiyah Dzihni Mudhiah; Jannah, Nazwa Raudatul; Nazwa Livia Maulisa; Abiyyu Ramadhan Putra Setiawan; Indah Andriyani Siregar; Derry Dardanella (Jurnal Sosial Terapan, 2025)
This study discusses the design of a database system for UMKM Milkshake Pakuan to improve operational efficiency in managing sales, stock inventory, and data-driven decision-making. The research includes needs analysis, database schema design, and the identification of information systems required to optimize operations. The designed database system is expected to reduce reliance on manual management and enhance the speed and accuracy of business processes. The research uses a descriptive quantitative method, with sales data collected over one week, direct surveys of operational processes, and interviews with the owner to understand the challenges in managing sales data and stock inventory. Keywords: MSMEs, Microsoft Access, Database, Query, Form